Kurikulum Pendidikan Islam Perspektif Al-Ghozali - Nasihudin, Muhammad (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2019)
According to Al-ghazali education is a human means to get closer to God through the path of science It is with science that humans in their social lives have degrees. Basically, education has a variety of purposes, but according to al-Ghazali who has a Sufistic understanding focuses all angular goals of worship on God.This can be seen from his view of educational material that joins between the mind and morality as a unity in the learning process.In his eyes, education is not only about the provision of knowledge but is more to the effect of the provision of knowledge. Therefore, the method he uses also combines 3 elements namely Psychological, Sociological and Pragmatic, so that the realization of an ideal education. Keywords: Curriculum, Education